Potentially Hazardous Drug-Drug Interactions Associated With Oral Antineoplastic Agents Prescribed in Chinese Tertiary Care Teaching Hospital Settings: A Multicenter Cross-Sectional Study - Wang, Haitao; Shi, Haitao; Wang, Yan; Wang, Na; Li, Youjia; Yang, Qianting; Li, Ya; Liu, Chenwei; Zan, Ying; Feng, Siping; Xie, Jiao (Frontiers in Pharmacology, 2022)
Background: Oral administration increases the risk of interactions, because most oral antineoplastic agents (OAAs) are taken on a daily basis. Interactions can increase exposure to antitumoral agents or cause treatment failure. Potential drug–drug interactions (DDIs) are commonly observed in patients with cancer, while the extent to which OAAs related hazardous DDIs remains unclear. Methods: We studied the contraindication patterns between oral antineoplastic agents and other medications among cancer patients in two tertiary care teaching hospitals in China. A total of 20 clinically significant hazardous DDI pairs that involved 30 OAAs were identified based on the predetermined criteria. Patient medications were checked for DDIs by using the US Food and Drug Administration approved labeling. Descriptive statistics and uni- and multivariate logistic regression analyses were carried out. Results: In this study, 13,917 patients were included and a total of 297 DDIs were identified. The results revealed that proton pump inhibitors (PPIs), dexamethasone and fluoroquinolones were the most often involved hazardous DDIs with OAAs. The most prevalent contraindication is the simultaneous use of certain molecular targeted agents and PPIs. In the result of the multivariate analysis, younger age (0–20 group), increasing number of drugs and patient treated with targeted therapy had a higher risk for DDIs. Conclusion: The prevalence of OAAs related hazardous DDIs appears to be low in the cancer patients. However, physicians and clinical pharmacologists should be aware of the potential hazardous DDIs when prescribing OAAs, especially certain pH-dependent molecular targeted agents and potential QTc prolonging drugs.